Resolving cryptic diversity in the Chromis viridis species complex (Pomacentridae): a multilocus phylogenetic and morphometric reassessment of species boundaries - M. U. Rekha; Teena Jayakumar T. K.; Abhilash C. P.; Ahamed Rasheeq A.; Saikrishnan K. R.; Vallarasu R.; Gladston Y.; Kajal Chakraborty; Ajithkumar T. T. (Frontiers in Marine Science, 2026)
The blue-green damselfish, Chromis viridis (Cuvier, 1830), is widely distributed across Indo-Pacific coral reefs and is among the most heavily traded marine ornamental fishes. Recent molecular studies have suggested the presence of cryptic diversity within the C. viridis complex, but species boundaries remain unresolved. Multilocus phylogenetic analyses incorporating three mitochondrial markers—cytochrome c oxidase subunit I (COI), cytochrome b (cytb), and the mitochondrial control region (D-loop)—and two nuclear markers, recombination-activating gene 1 (RAG1) and recombination-activating gene 2 (RAG2), were performed to assess lineage diversification within the Chromis viridis species complex. Specimens collected from the Lakshadweep Archipelago and the Gulf of Mannar, India, formed a distinct and well-supported lineage that was clearly separated from C. viridis sensu stricto and other congeners in phylogenetic reconstructions and genetic distance analyses. Multiple species-delimitation approaches consistently supported the recognition of this lineage as an independently evolving taxon, and morphometric analyses revealed corresponding differences in body proportions and meristic characters. Based on the concordance of molecular and morphological evidence, a new species, Chromis veneta sp. nov., is herein described from the Indian Ocean. The new species differs from C. viridis in having a relatively elongate body, narrower caudal peduncle, distinctive body pigmentation, yellowish to orangish distal fin margins, and a deeply forked caudal fin with elongate lobe tips. Additional diagnostic features include differences in dentition, gill-raker counts and sagittal otolith morphology. The discovery of C. veneta sp. nov. highlights underestimated diversity within the C. viridis complex and underscores the importance of integrative taxonomy in revealing cryptic reef-fish diversity.

Unveiling Growth Patterns and Condition Status of 25 Flatfish Species (Order: Pleuronectiformes) from the Southern Coast of Tamil Nadu, India: Evidence from Length–Weight Relationships - R. G. Sasikumar; P. Jawahar; N. Jayakumar; G. Arul Oli; T. Ravikumar; M. Sharumathi; J. Joyson Paul; C. Abishek; Arnaa Armaan Muzaddadi (Thalassas: An International Journal of Marine Sciences, 2026)

Deciphering Environmental Drivers on Plankton Dynamics in Punnakayal–Pazhayakayal Estuarine Complex, Southern Coast of India - Kamei Ringjonmeilu; N. Jayakumar; R. Durairaja; V. Rani; T. Ravikumar; R. Saravanan; C. Sudhan; Adyasha Sahu; J. Joyson Paul; S. Parkavi (Thalassas: An International Journal of Marine Sciences, 2026)

Comparative Assessment of Length-Weight Relationship and Relative Condition Factor of 25 Grouper Species along the Southern Coast of Tamil Nadu, India - J. Joyson Paul; R. Durairaja; N. Jayakumar; N. Daniel; T. Ravikumar; M. Sharumathi; R. G. Sasikumar; C. Abishek; Arnaa Armaan Muzaddadi (Thalassas: An International Journal of Marine Sciences, 2026)

Exploring the Generalization Limits of UNet Variants in Road Extraction - T. V. Jayakumar; Deepak Mishra; M. Ramiya Anandakumar; Jai G. Singla (Journal of the Indian Society of Remote Sensing, 2026)

Correction: Naringin Potentiates Docetaxel-Induced Apoptosis in Breast Cancer Cells via Transient Interaction with the TUBB3 GTP-Binding Site - Miguel Kativa; Agilan Balupillai; T. Jayakumar; Joen-Rong Sheu (Cell Biochemistry and Biophysics, 2026)

Naringin Potentiates Docetaxel-Induced Apoptosis in Breast Cancer Cells via Transient Interaction with the TUBB3 GTP-Binding Site - Miguel Kativa; Agilan Balupillai; T Jayakumar; Joen-Rong Sheu (Cell Biochemistry and Biophysics, 2026)

Aquaculture of Asian seabass (Lates calcarifer) in India: A comparative economic analysis across production systems and regions - Geetha R.; Abhinaya D.; Naffees Gowsar S. R.; Ravisankar T.; Kailasam M.; Jayakumar R.; Subburaj R.; Shinoj P.; Rajni Jain; Lal K. K.; Patil P. K. (Aquaculture International, 2025)

The role of macroalgae in modulating coral calcification: Mixed species responses in a changing reef environment - B. Manikandan; P. Sawant; P.K. Maurya; Ashish Pal; T.A. Naik; J. Ravindran; Sayeri Paul; T. Lad; S. Prabhudesai; K. Jayakumar (Marine Environmental Research, 2025)

Stratified enhanced interval-valued q-rung orthopair picture bipolar fuzzy decision-making approach for municipal solid waste disposal technique selection - T. N. Parthasarathy; C. S. Thilagasree; T. Jayakumar; V. Simic; D. Pamucar (International Journal of Environmental Science and Technology, 2025)

Assessment of extreme rainfall events for iFLOWS Mumbai in NCUM regional forecasting system - Mohan S. T; Raghavendra Ashrit; Kondapalli Niranjan Kumar; Upal Saha; D. Nagarjuna Rao; A. Jayakumar; Saji Mohandas; V. S. Prasad (Natural Hazards, 2024)

Influencing factors and environmental feasibility analysis of agricultural waste preprocessing routes towards biofuel production – A review - Selvakumar Periyasamy; Adane Asefa Adego; P. Senthil Kumar; G.G. Desta; T. Zelalem; V. Karthik; J. Beula Isabel; Mani Jayakumar; Venkatesa Prabhu Sundramurthy; Gayathri Rangasamy (Biomass and Bioenergy, 2024)

Editorial: Recent developments in oxygen minimum zones biogeochemistry - Annie Bourbonnais; Sudheesh Valliyodan; Mark A. Altabet; Amal Jayakumar; Syed Wajih Ahmad Naqvi; Gireesh Kumar T. R. (Frontiers in Marine Science, 2023)

Etiology behind canine uterine inertia: Role of uterine expression of MLCK4, MYH2, and PKC genes - Magnus P.K.; Jayakumar C.; Naicy T.; Lali F.A.; Hiron M. Harshan; Abhilash R.S.; Ajithkumar S. (Animal Reproduction Science, 2023)

Impact of duration of stunting on compensatory growth and biometrics of snubnose pompano, Trachinotus blochii (Lacepede,1801) in low saline conditions - P. P. Suresh Babu; A. Anuraj; J. Loka; N. D. Praveen; K. Srinivasa Rao; M. T. Shilta; K. K. Anikuttan; R. Jayakumar; A. K. Abdul Nazar; I. Boby; J. Imelda (Thalassas: An International Journal of Marine Sciences, 2022)

A new species of Congrid eel, Ariosoma melanospilos sp. nov., from Indian waters with taxonomic description of A. dolichopterum (Congridae: Bathymyrinae) - Paramasivam Kodeeswaran; T. K Teena Jayakumar; S. Akash; T. T. Ajith Kumar; Kuldeep Kumar Lal (Marine Biodiversity, 2021)

Genome-wide discovery of SNPs in candidate genes related to production and fertility traits in Sahiwal cattle - M. R. Vineeth; T. Surya; Jayakumar Sivalingam; Anshuman Kumar; S. K. Niranjan; S. P. Dixit; Karanveer Singh; M. S. Tantia; I. D. Gupta (Tropical Animal Health and Production, 2020)

First Record of the Rare Eel Bathymyrus simus Smith 1965 (Anguilliformes: Congridae) from the Indian Ocean with a Taxonomic Description - T. K. Teena Jayakumar; T. T. Ajith Kumar; Kuldeep K. Lal (Thalassas: An International Journal of Marine Sciences, 2020)

Correction to: Antimicrobial Drugs Encapsulated in Fibrin Nanoparticles for Treating Microbial Infested Wounds - B. Maria Alphonsa; P. T. Sudheesh Kumar; G. Praveen; Raja Biswas; K. P. Chennazhi; R. Jayakumar (Pharmaceutical Research, 2019)

Transdermal Delivery of Functional Collagen Via Polyvinylpyrrolidone Microneedles - Wenchao Sun; Mohammed Inayathullah; Martin A. C. Manoukian; Andrey V. Malkovskiy; Sathish Manickam; M. Peter Marinkovich; Alfred T. Lane; Lobat Tayebi; Alexander M. Seifalian; Jayakumar Rajadas (Annals of Biomedical Engineering, 2015)

Urinary semaphorin 3A correlates with diabetic proteinuria and mediates diabetic nephropathy and associated inflammation in mice - Riyaz Mohamed; Punithavathi Ranganathan; Calpurnia Jayakumar; Ferdau L. Nauta; Ron T. Gansevoort; Neal L. Weintraub; Michael Brands; Ganesan Ramesh (Journal of Molecular Medicine, 2014)

Antimicrobial Drugs Encapsulated in Fibrin Nanoparticles for Treating Microbial Infested Wounds - B. Maria Alphonsa; P. T. Sudheesh Kumar; G. Praveen; Raja Biswas; K. P. Chennazhi; R. Jayakumar (Pharmaceutical Research, 2014)

Lead time for medium range prediction of the dry spell of monsoon using multi-models - A JAYAKUMAR; VINAY KUMAR; T N KRISHNAMURTI (Journal of Earth System Science, 2013)

Information processing bottlenecks in macaque posterior parietal cortex: an attentional blink? - Ryan T. Maloney; Jaikishan Jayakumar; Ekaterina V. Levichkina; Ivan N. Pigarev; Trichur R. Vidyasagar (Experimental Brain Research, 2013)

Mechanism of intraseasonal oceanic signature in the region off southern tip of India during boreal summer - A. Jayakumar; C. Gnanaseelan; T. P. Sabin (International Journal of Climatology, 2013)
Sea surface temperature (SST) in the region off southern tip of India (STI, 75–83°E, 5–8°N) exhibited a prominent variability in the intraseasonal time scale (both 30–90 d and 10–30 d band) during boreal summer. Mechanisms associated with this intraseasonal variability are studied using three‐dimensional ocean general circulation model (OGCM) sensitivity experiments, satellite observed outgoing longwave radiation, SST and winds for the period 1998–2007. The background oceanic structure of the STI characterized by a shallow thermocline and moderate mixed layer provided ideal conditions for strong oceanic sub‐surface processes. The model mixed layer heat budget reveals that the oceanic processes such as horizontal advection and vertical processes are the dominant mechanisms in the STI region as compared with air‐sea flux. Sensitivity experiments with the OGCM reveals that the ocean dynamical processes contribute to most of the intraseasonal SST variability and the wind stress contributes to 85% of the variability whereas surface flux contributes to only 15% for the 30–90 d SST variability. Higher amplitude of surface flux perturbation and its contribution to SST in the 10–30 d as compared with the 30–90 d band are evident in the model experiment and are consistent with the observational analysis. There is year‐to‐year variability in the relative role of horizontal and vertical processes for different intraseasonal SST events over STI.

Evaluation of Wound Healing Potential of β-Chitin Hydrogel/Nano Zinc Oxide Composite Bandage - Sudheesh Kumar P. T.; Vinoth-Kumar Lakshmanan; Mincy Raj; Raja Biswas; Tamura Hiroshi; Shantikumar V. Nair; Rangasamy Jayakumar (Pharmaceutical Research, 2013)

Real time remote monitoring of air pollutants and their online transmission to the web using internet protocol - Y. Anjaneyulu; I. Jayakumar; V. Hima Bindu; P. V. Mukunda Rao; G. Sagareswar; K. V. Ramani; T. H. Rao (Environmental Monitoring and Assessment, 2007)

Rapid assessment on the impact of tsunami on mangrove vegetation of The Great Nicobar Island - R. Sridhar; T. Thangaradjou; L. Kannan; A. Ramachandran; S. Jayakumar (Journal of the Indian Society of Remote Sensing, 2006)

Effect of time and mode of application of potassium on the growth, yield and quality of sugarcane ratoon - Thomas Mathew; T. M. Kurian; Babu George; Sosamma Cherian; Jessy M. Kuriakose; K. Sreekumar; G. Jayakumar (Sugar Tech, 2004)

Residual effects of sulphur nutrition on the ratoon crop of sugarcane - Thomas Mathew; T. M. Kurian; Sosamma Cherian; G. Jayakumar (Sugar Tech, 2003)

Isotopic composition of nitrate in the central Arabian Sea and eastern tropical North Pacific: A tracer for mixing and nitrogen cycles - Jay A. Brandes; Allan H. Devol; T. Yoshinari; D. A. Jayakumar; S. W. A. Naqvi (Limnology and Oceanography, 1998)
The δ 15 N composition of nitrate and N 2 gas was measured in the eastern tropical North Pacific (ETNP) and central Arabian Sea (AS) suboxic regions. The δ 15 N of nitrate increased from 6‰ at 2,500 m to 15‰ at 250–350 m in both regions, while the δ 15 N of N 2 concurrently decreased from 0.6‰ to 0.25‰. The denitrification isotopic fractionation factor (ε denit ) for each region was estimated using both advection‐reaction and diffusion‐reaction models. Values for ε denit in the ETNP ranged from 25 ± 2 (advection‐reaction) to 30 ± 3 (diffusion‐reaction). Values for ε denit in the central AS varied from 22 ± 3 (advection‐diffusion) to 25 ± 4 (reaction‐diffusion) using a starting nitrate isotopic composition of 6‰ but were indistinguishable from calculated values from the ETNP when an initial value of 5‰ was employed. Based upon the model results, an average global ε denit of 27 ± 3 is proposed for marine suboxic water columns. Isotopic enrichment of nitrate in oxic waters beneath the active denitrification regions was observed and indicates the presence of significant cross‐isopycnal ventilation at depth. The isotopic composition of nitrate decreased above 250 m to −80 m, and this pattern is hypothesized to be caused by the input of isotopically light nitrogen from nitrogen fixation in the euphotic zone. A simple isotopic mass balance indicates that a significant percentage of primary productivity in the central AS may be fueled by nitrogen fixation.

Energy metabolism and mechanical recovery after cardioplegia in moderately hypertrophiedrats - Ryszard T. Smolenski; Jay Jayakumar; Anne-Marie L. Seymour; Magdi H. Yacoub (Molecular and Cellular Biochemistry, 1998)

Latex immunoassay for rapid detection of newcastle disease virus - G. Thirumurugan; R. Jayakumar; K. Kumanan; A. T. Venugopalan; K. Nachimuthu (Tropical Animal Health and Production, 1997)